Simulation of sub-bituminous coal hydrodynamics and thermochemical conversion during devolatilization process in a fluidized bed. (5th May 2018) - Salmasi, A.; Shams, M.; Chernoray, V.
Highlights: CPD model predicts devolatilization time and mass loss of the fuel particle well. The effect of bed material is considered on devolatilization process in fluidized bed. There is a good agreement between the numerical and experimental results. Eulerian-Eulerian-Lagrangian approach is capable to predict hydrodynamics of bed. Fuel particle movement is mostly in vertical direction due to bubble eruption. Abstract: The majority of the numerical studies conducted on the thermochemical conversion of solid fuels in a fluidized bed have ignored the bed materials inside the bed and just considered the effect of hot air passing the fuel particle. In this study, a sub-bituminous coal particle hydrodynamics during the devolatilization process is modeled inside a 2D fluidized bed in two different cases. In the first case, the energy exchange of inert phase with the fuel particle is included in the simulation and, in the second case, it is ignored. The coal particle's motion is modeled including the drag force from the bed and the heat and the mass transfer are also simulated during the devolatilization process while the fuel particle is heated up using the chemical percolation devolatilization model. The simulation successfully predicted the motion of the particle inside the bed as well as the temperature increase and volatile release from the particle during the simulation time. The mass loss and temperature history of the fuel particle resulting from the simulation show good agreement with the experimental results. The simulation also indicates that inert particles have a great effect on the heat transfer coefficient inside the bed and ignoring them will cause a difference in the devolatilization time, and this difference will also increase significantly with the increase of the fuel particle's diameter.